3D-printed spider-web structures for highly efficient water collection. Issue 8 (August 2022) - Guo, Chi; Wang, Chengquan; Huang, Qi; Wang, Zhi; Gong, Xiaojing; Ramakrishna, Seeram
Abstract: Fog and moisture in nature are important freshwater resources, and the collection of these fog water is of great significance to arid regions. Inspired by the unique geometric structure of the spindle knot on spider silk, artificial fibers with periodic structures have been fabricated for water collection, which can effectively alleviate the problem of water shortage in arid areas. Traditional manufacturing methods are difficult to replicate the true shape of the spindle knot, and related research has encountered a bottleneck in improving water collection efficiency. 3D printing technology, which is different from traditional subtractive manufacturing, can directly replicate spider silk with periodic knots, making it possible to study water collection by artificial spider webs of various designs. Here, 3D printing technology is used to fabricate artificial spider webs with different geometric structures for efficient transportation and collection of water. In addition, the artificial spider web is treated with hydrophilic surfaces. In the humid environment for 2 h, the spider web with convex-concave multi-size spindle knots and multi-curvature connections has a maximum water collection capacity of 6.2g, and the mass of water collection is 35% higher than the existing best water collection artificial fibers. This work provides a sustainable and environmentally friendly route for the effective collection of humid air, and has certain reference value for the development of environmentally friendly water collection equipment. Graphical abstract: Image 1 Highlights: Spindle structure re-optimization and design on spider silk. The convenience of 3D printing technology and the precision of microstructures. The spindle structure on spider silk plays a crucial role in the water-harvesting properties of spider webs. Abstract : Water harvesting; Biomimetic; 3D printing; Artificial spider web.